Speleological Insights into Bestoon Cave: A Case Study from the Bradost Mountain, Northeastern Iraq (Iraqi National Journal of Earth Science (INJES), 2026)
The Bestoon Cave represents a geologically and archaeologically important karstic system formed within the Upper Cretaceous Bekhme Formation through long-term carbonate dissolution and secondary mineral deposition. The cave is located near the top of Mount Bradost in the Iraqi Kurdistan Region at an altitude of 1506 meters above sea level. This research investigates the cave’s speleogenetic processes, microfabric features, and paleoclimatic significance through analyses of speleothems including flowstones, stalactites, and stalagmites. Microfabric analysis using a LEICA DM4500P polarizing light microscope for (BST-1 and BST-2) reveals distinct mineral assemblages such as dense columnar calcite, microcrystalline CaCO3, and dendrite crystal fabrics indicating fluctuating hydrological and climatic conditions. The presence of various speleothem morphologies including soda flakes, drapery, shields, cave boxwork, cave popcorn, rimstone dam, and cave pearl provides insights into the conditions of mineral deposition and water chemistry during their formation. In terms of geochemical analysis, sample BST-1 consists of 90% aragonite and 10% calcite, where the presence of calcite indicates that the original aragonitic speleothem material underwent partial recrystallization or diagenetic transport. High aragonite indicates deposition under stable conditions such as rapid precipitation from supersaturated fluids and temperature fluctuations. The sample BST-2 is composed of 100% calcite, suggesting that the mineral was formed under stable conditions favoring calcite precipitation.
Keywords: Bestoon, Speleothem, Cave, Microfabrics, Bradost.